Negotiating Universality: Islam and Local Culture - Cut Linda Marheni; Zumadil (Lembaga Swadaya Masyarakat Asosiasi Masyarakat Madani Indonesia (AMMI), 2026)
This essay explores the relationship between the universal Islamic theory and local cultural expression through the case of Islam Nusantara. The article, through qualitative thematic analysis of religious discourse and participant narratives, argues that the main argument is not about a particular Indonesian jargon but about how Muslims interpret authentic Islam in different social and historical contexts. The findings support two main perspectives: a universalist approach that stresses a single normative Islam derived from revelation and classical jurisprudence; and a contextualist one that allows for local adaptation provided that it does not contravene Sharia. This essay also reveals that many arguments on both sides draw from similar sources such as the Qur’an, prophetic tradition, legal maxims, and statements concerning Islamic history. Islam Nusantara is best understood as one instance in a larger ummah-level debate on orthodoxy, plurality, authority and cultural mediation.